Hybrid lymph node imaging using 64Cu-labeled mannose-conjugated human serum albumin with and without indocyanine green. Issue 10 (October 2015) - Kang, Choong Mo; An, Gwang Il; Choe, Yearn Seong
<x xml:space="preserve">Abstract</x> Objective Human serum albumin (HSA), which has 58 Lys residues, one Cys residue, and indocyanine green (ICG) adsorption sites, can be used as a multifunctional platform for the development of hybrid imaging probes. In this study, we prepared 64Cu-labeled mannose-conjugated HSA with and without ICG ([64Cu]1-ICG and [64Cu]1, respectively) and compared hybrid PET/near-infrared fluorescence (NIRF) imaging with positron emission tomography (PET)/Cerenkov luminescence (CL) imaging of lymph nodes (LNs). Materials and methods 1, 4, 7, 10-Tetraazacyclododecane-N, N′, N′′, N′′′-tetraacetic acid (DOTA)/mannose-conjugated HSA (1) was synthesized by conjugating mannose molecules to Lys residues and a DOTA molecule to a Cys residue of HSA. Compound 1 was then labeled with 64Cu ([64Cu]1), and the resulting [64Cu]1 was adsorbed with ICG ([64Cu]1-ICG). PET/NIRF or PET/CL imaging and subsequent biodistribution studies were performed in ICR mice after injection of the probes into the foot pads. Results The numbers of mannose and DOTA molecules conjugated to HSA were 7.17±0.49 and 0.95±0.18, respectively. The site-specific conjugation of one DOTA molecule to HSA was sufficient for 64Cu-labeling with high efficiency (96.0±1.1%). PET/NIRF and PET/CL imaging and subsequent biodistribution studies demonstrated that the probes were avidly taken up by the popliteal LNs (PO), with a slightly higher uptake ratio of the PO to the lumbar LNs by [64Cu]1. Conclusion In-vivo studies suggest that [64Cu]1 has more specific and selective binding to mannose receptors in the PO than [64Cu]1-ICG.